Plackett-Burman Design for rGILCC1 Laccase Activity Enhancement in Pichia pastoris: Concentrated Enzyme Kinetic Characterization. (21st March 2017) - Morales-Álvarez, Edwin D.; Rivera-Hoyos, Claudia M.; Cardozo-Bernal, Ángela M.; Poutou-Piñales, Raúl A.; Pedroza-Rodríguez, Aura M.; Díaz-Rincón, Dennis J.; Rodríguez-López, Alexander; Alméciga-Díaz, Carlos J.; Cuervo-Patiño, Claudia L.
Abstract : Laccases are multicopper oxidases that catalyze aromatic and nonaromatic compounds with concomitant reduction of molecular oxygen to water. They are of great interest due to their potential biotechnological applications. In this work we statistically improved culture media for recombinant GILCC1 (rGILCC1) laccase production at low scale from Ganoderma lucidum containing the construct pGAPZ α A- GlucPost -Stop in Pichia pastoris . Temperature, pH stability, and kinetic parameter characterizations were determined by monitoring concentrate enzyme oxidation at different ABTS substrate concentrations. Plackett-Burman Design allowed improving enzyme activity from previous work 36.08-fold, with a laccase activity of 4.69 ± 0.39 UL −1 at 168 h of culture in a 500 mL shake-flask. Concentrated rGILCC1 remained stable between 10 and 50°C and retained a residual enzymatic activity greater than 70% at 60°C and 50% at 70°C. In regard to pH stability, concentrated enzyme was more stable at pH 4.0 ± 0.2 with a residual activity greater than 90%. The lowest residual activity greater than 55% was obtained at pH 10.0 ± 0.2. Furthermore, calculated apparent enzyme kinetic parameters were a V m a x of 6.87 × 10 −5  mM s −1, with an apparent K m of 5.36 × 10 −2  mM. Collectively, these important stability findings open possibilities for applications involving a wide pH and temperature ranges.